Pan-Phosphodiesterase Inhibitors Attenuate TGF-β-Induced Pro-Fibrotic Phenotype in Alveolar Epithelial Type II Cells by Downregulating Smad-2 Phosphorylation - Katarzyna Wójcik-Pszczoła; Grażyna Chłoń-Rzepa; Agnieszka Jankowska; Bruno Ferreira; Paulina Koczurkiewicz-Adamczyk; Elżbieta Pękala; Elżbieta Wyska; Krzysztof Pociecha; Reinoud Gosens (MDPI AG, 2022)
Airway remodeling is a pathological process that accompanies many chronic lung diseases. One of the important players in this process are epithelial cells, which under the influence of pro-inflammatory and pro-fibrotic factors present in the airway niche, actively participate in the remodeling process by increasing extracellular matrix secretion, acquiring migration properties, and overproducing pro-fibrotic transducers. Here, we investigated the effect of three new 8-arylalkylamino- and 8-alkoxy-1,3-dimethyl-2,6-dioxo-1,2,3,6-tetrahydro-7H-purin-7-yl-N-(5-(tert-butyl)-2-hydroxyphenyl)butanamides (1, 2, and 3), representing prominent pan-phosphodiesterase (pan-PDE) inhibitors on transforming growth factor type β (TGF-β)-induced alveolar epithelial type II cells (A549 cell line) of a pro-fibrotic phenotype. Our results demonstrate for the first time the strong activity of pan-PDE inhibitors in the prevention of TGF-β-induced mesenchymal markers' expression and A549 cells' migration. We also showed an increased p-CREB and decreased p-Smad-2 phosphorylation in TGF-β-induced A549 cells treated with 1, 2, and 3 derivatives, thereby confirming a pan-PDE inhibitor mesenchymal phenotype reducing effect in alveolar epithelial type II cells via suppression of the canonical Smad signaling pathway. Our observations confirmed that PDE inhibitors, and especially those active against various isoforms involved in the airway remodeling, constitute an interesting group of compounds modulating the pro-fibrotic response of epithelial cells.